2014
DOI: 10.1186/ar4450
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of endothelial dysfunction in rheumatoid arthritis: lessons from animal studies

Abstract: Rheumatoid arthritis (RA) is a chronic systemic inflammatory disease characterized by articular and extra-articular manifestations involving cardiovascular diseases (CVDs), which account for 30% to 50% of all deaths. In patients with RA, atherosclerosis lesions occur earlier and have a more rapid evolution than in the general population. Beyond mortality, the impact of CVD on quality of life, combined with the associated increase in health-care costs, renders CVD in RA a major public health problem. Recent stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 48 publications
6
39
0
1
Order By: Relevance
“…In conduit arteries, our results demonstrated that endothelial dysfunction was absent at the preclinical stage and during very early AIA but became evident at the time of acute clinical inflammation (day 33). These data are consistent with previous results obtained in animal models of RA and in RA patients .…”
Section: Discussionsupporting
confidence: 93%
“…In conduit arteries, our results demonstrated that endothelial dysfunction was absent at the preclinical stage and during very early AIA but became evident at the time of acute clinical inflammation (day 33). These data are consistent with previous results obtained in animal models of RA and in RA patients .…”
Section: Discussionsupporting
confidence: 93%
“…ED leads to increase in permeability to inflammatory cells such as monocytes. On the other hand, this endothelial dysfunction is associated with increased expression of adhesion molecules and inflammatory cytokines, which facilitate penetration of monocytes to the sub‐endothelium . In a mouse model of RA it has been shown that acetylcholine‐induced endothelium vasorelaxation was decreased .…”
Section: Relation Between Atherosclerosis and Ramentioning
confidence: 99%
“…On the other hand, this endothelial dysfunction is associated with increased expression of adhesion molecules and inflammatory cytokines, which facilitate penetration of monocytes to the sub‐endothelium . In a mouse model of RA it has been shown that acetylcholine‐induced endothelium vasorelaxation was decreased . On the other hand, proper function of the endothelium depends on the equilibrium between vasoconstrictors such as angiotensin II (ANG‐II), thromboxane A2 (TXA2) and endothelin‐1 and vasodilator substances such as prostacyclin (PGI2), nitric oxide (NO) and endothelium‐derived hyperpolarizing factors (EDHFs) .…”
Section: Relation Between Atherosclerosis and Ramentioning
confidence: 99%
“…Data about endothelial mechanisms involved in ED have been provided by studies on animal models of RA. As reported in a recent review [23], RA-associated ED is secondary to decreased NO availability, decreased endothelial NOS expression/activity, uncoupling of endothelial NOS, increased arginase activity, excess of superoxide anion production, impaired EDHF production, increased synthesis of prostanoids and increased angiotensin II production.…”
Section: Endothelial Dysfunction In Ramentioning
confidence: 99%